Kajian Naskah Drama Lumpur Kemiskinan Karya Marjan Fariq Menggunakan Pendekatan Pragmatik - Sevti Putri Thavany; Bintang Putri Pamungkas; Hesti Nurlinda; Adita Widara Putra (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research aims to examine the manuscript of Lumpur Kemiskinan by Marjan Fariq which is an adaptation of the short story Gerobak by Seno Gumira Ajidarma using a pragmatic approach. The research method used is descriptive-qualitative. The data collection techniques used to obtain data are reading, note-taking and research techniques from various literature. The results of the research show that the drama drama Lumpur Kemiskinan by Marjan Fariq has many life values that can be learned by readers, namely a) having a sense of empathy and caring for fellow humans, b) being sensitive to things around you, c) don't always have negative prejudices. towards other people, d) avoid selfishness which can harm other people, e) respect each other without feeling superior, f) don't always depend on other people, and g) always be grateful for the good fortune you have obtained.